Beginning SQL server 2008 administration - Walters, Robert E. (Expert's voice in SQL server., 2009)
"Beginning SQL Server 2008 Administration is essential for anyone wishing to learn about implementing and managing SQL Server 2008 database. This book will bring all readers up to speed on the enterprise platform Microsoft SQL Server 2008"--Resource description page